ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DALAM PEMBAYARAN REKENING LISTRIK (Studi Pada Unit Pelayanan Pelanggan di Probolinggo) - Willy Tri Hardianto; Agung Suprojo; Bernardus Rettob (Universitas Tribhuwana Tunggadewi, 2012)
Customer satisfaction is feeling happy or disappointed someone who emerged after comparing the performance (results) are considered products of the expected performance. Customer satisfaction is influenced by perceptions of a variety of good quality services and products. One of the factors that determine customer satisfaction is the customer perception of service quality which focuses on five dimensions of quality of service that is physical evidence (tangible), reliability, responsiveness, insurance, and empathy. One organization that is engaged in public service to the PT. PLN (Persero) in Probolinggo. Types of services provided to the public one of them is Payment Point Online Bank (PPOB) is counter receipt (payment points) payment of electricity bills of PLN customers who directly online with the bank. Banks appointed for the provision of electric service bill payment one of them BRI (Bank Rakyat Indonesia).